Designing Services for Performance- Part I How to make sure your services keep up. - Linthicum, David
Performance is often an afterthought when building new systems and I'm finding that services are no exception. Truth be told, most services out there just function. They are not optimized to scale, and SOAs are running into walls as those services hit the upper limit. If we don't learn to solve this problem, many SOAs simply won't get off the ground.